PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN PROGRAM LITERACY FAMILY SEBAGAI MEDIA BELAJAR DI MASA PANDEMI - Sitti Rachmi Massie; Herman Didipu (Univeristas Negeri Gorontalo, 2022)
This program aims to empower the community in improving human resources through the family literacy program. Variety of internet media literacy which is the main treat for students. This challenge is also an opportunity for all about how the use of technology can help bring students or other learners to be competent for the 21st century. The most important skill in the 21st century is recognizing the forms of literacy in the environment. The Village Development Program will lead to improving the education system during the pandemic. Through the Empowerment of the Litercy Family Program in improving the quality of education, it is hoped that there will be synergy between the government, schools, committees and the community in improving the quality of learning at school or at home.